Yangon Peri-Urban Poultry Farmer Phone Survey 2020 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Yangon Peri-Urban Poultry Farmer Survey, conducted in 2020, assessed the impact of the COVID-19 pandemic on poultry production. This phone-based survey was carried out in six rounds: the first four rounds were conducted biweekly in June and July 2020, while the fifth and sixth rounds took place in August and November, respectively. The survey focused on a subsample of 269 chicken farms, comprising 190 broiler farms and 79 layer farms, from the 2019 Yangon Peri-Urban Livestock Survey. This subsample included all broiler and layer farms from the original survey that were reachable by phone and consented to participate. Among the surveyed farms, 74% of the broiler farms and 52% of the layer farms were integrated with fishponds. The questionnaire gathered data on farm operational status, business operations, and business sentiment.